The SDEMMA model for galactic cosmic ray and its dosimetric application - Xiaojian Song; Ran Huo; Songying Xu; Songying Xu; Xuemei Chen; Xuemei Chen; Xi Luo (Frontiers in Astronomy and Space Sciences)
IntroductionFuture crewed missions to Mars will encounter substantially elevated radiation levels compared to low Earth orbit operations. To address this challenge, we present the Space-Dependent Energetic cosmic ray Modulation using MAgnetic spectrometer (SDEMMA) model, a novel framework for modeling galactic cosmic ray (GCR) dynamics in deep-space environments.MethodsThe model employs stochastic differential equations with outer boundary conditions derived from contemporary local interstellar spectrum models. Time-dependent diffusion and drift coefficients were optimized through Markov Chain Monte Carlo parameter fitting against 2006-2019 observational data from the space-borne magnetic spectrometers of AMS-02 and PAMELA.ResultsSDEMMA extends GCR spectral calculations to radial positions beyond 1.0 AU, explicitly resolving radial gradients under diverse heliospheric conditions. The framework provides spatiotemporally resolved GCR spectra for charge numbers Z=1–28 at rigidities >0.2 GV, covering the inner heliosphere between Earth and Mars and currently the 2006-2019 epoch.DiscussionImplementation demonstrates the model's operational utility: dose equivalent rates behind 30 g/cm2 polyethylene shielding during a flux minimum range from 14-17 cSv/yr, with variance attributable to quality factor selection.